Rapid Urbanization and Agricultural Intensification Increase Regional Evaporative Water Consumption of the Loess Plateau. Issue 23 (4th December 2020) - Liang, Wei; Zhang, Weibin; Jin, Zhao; Yan, Jianwu; Lü, Yihe; Li, Shuai; Yu, Qiang
Abstract: Changing evapotranspiration (ET) will impact freshwater availability, knowledge of which is a critical prerequisite for policy development related to water resources management in an evolving climate, especially for water‐limited regions. However, the socio‐economic effects are not considered due to the lack of detailed information about this. Here we used a well‐validated remote sensing model and multiple socio‐economic factors to investigate the driving factors of ET changes over the Loess Plateau during 1982–2012. Results showed that the modeled annual ET significantly increased by 2 mm yr −2 during this period ( p < 0.001), caused by increased transpiration (2.16 mm yr −2 ) and interception (0.27 mm yr −2 ), which was partly offset by decreased soil evaporation (−0.47 mm yr −2 ). Meanwhile, although the average ET of the forest was larger (480.4 ± 14.8 mm yr −1 ), it was found that the change in total ET of the region was dominated by that in grassland and cropland (1.1 km 3 yr −2, 90% altogether). Factorial simulations indicated that the intensifying ET over 79.4% and 9.1% of the study area can be explained by vegetation greening and climate change, respectively. Further analysis suggested that the vegetation greening and the increased ET were primarily associated with the rapid urbanization and agricultural intensification. Our findings highlight the potential unfavorable effects of socio‐economic activities on water resources management on this coupled natural‐human system that is already facing water scarcity issues. Key Points: Annual ET significantly increased, caused by increased transpiration and interception, which was partly offset by decreased soil evaporation Although the average ET of forest was larger, the change in total ET of the region was dominated by that in grassland and cropland Vegetation greening and the intensifying ET were primarily associated with the rapid urbanization and agricultural intensification